Gambaran Status Gizi Anak di Kota Kendari - Irma Yunawati; Wa Ode Salma; Nushriana Nurnashriana Jufri; Syakinah Jamustiara; Ananda Ramadani; Rahmawati Rahmawati; Wa Ode Elfi; Desi Apriyani; Dela Apriliana Pratiwi (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Background: Nutrition in primary school-aged children is an important issue that can affect their growth and development. In addition to undernutrition, the nutrition transition in Indonesia shows an increasing prevalence of overnutrition, including overweight and obesity, which is of increasing concern. Objectives: This study aimed to describe the nutritional status of children aged 7-13 years at SD 8 Baruga and SD 1 Poasia, Kendari City, and analyze the distribution of nutritional status by gender and age group. Methods: This study used a descriptive design with a cross-sectional approach. Data were collected through measurements of height (TB), weight (BW), and body mass index (BMI) on 50 students, consisting of 22 boys and 28 girls. Results: The results showed that the majority of respondents (68%) had normal nutritional status, while the prevalence of undernutrition was 2%, overweight 18%, and obesity 12%. Based on gender, overnutrition and obesity were more prevalent among girls (32.1%) than boys (22.7%). In terms of age group, overnutrition and obesity were most prevalent in the 9-12 years age group. Conclusion: The high prevalence of overnutrition shows an alarming, although the prevalence of undernutrition is lower than the average for Southeast Sulawesi.